PENGARUH KOMPETENSI TERHADAP KINERJA TIM - Andi Hendrawan; Aneu Yulianeu; Kristian Cahyandi (Journal of Management Review, 2018)
The organization is currently in a peace-filled environment. The speed of product development, customer response, and troubleshooting can all have a dramatic effect on organizational and team performance levels.The research aims to prove the influence of team competence dimensions on team performance. So that will be obtained picture Dimension where the most influential in team performance. The study used a sample of 40 teams selected by Random Sampling Method of 130 UMKM (Small and Medium Micro Enterprises) engaged in various fields. The data were collected by questionnaire, observation, and interview. The research instrument used a Likert scale that has been modified by Likert scale. The results showed that: knowledge influenced to team performance (accepted), skill influence to team performance (rejected), nature-influenced to team performance (accepted) and motivation influence to team performance (accepted).